2014
DOI: 10.1177/1932296814558348
|View full text |Cite
|
Sign up to set email alerts
|

Lipoatrophy in Children With Type 1 Diabetes

Abstract: The objectives were to evaluate the current prevalence of lipoatrophy at insulin injection sites in young patients with type 1 diabetes. Standardized examination of insulin injection sites in all 678 patients with type 1 diabetes treated in 2013 in our outpatient clinic were conducted. In case of lipoatrophy photo documentation and standardized interview with parents and patients were performed. We identified a total of 16 patients (43.8% male) with lipoatrophy (overall prevalence 2.4%). The current mean age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
2
18
0
2
Order By: Relevance
“…Lipohypertrophy, or local fat accumulation, at the site of insulin administration, is another issue that is frequently encountered with pump therapy . Fat loss at the site of prior insulin infusion sites, lipoatrophy, is less common and has been seen more frequently in those with multiple autoimmune diseases . Both of these findings are categorized as lipodystrophy and earlier studies have shown a greater risk of these issues in those with higher insulin autoantibodies .…”
Section: Insulin Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipohypertrophy, or local fat accumulation, at the site of insulin administration, is another issue that is frequently encountered with pump therapy . Fat loss at the site of prior insulin infusion sites, lipoatrophy, is less common and has been seen more frequently in those with multiple autoimmune diseases . Both of these findings are categorized as lipodystrophy and earlier studies have shown a greater risk of these issues in those with higher insulin autoantibodies .…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…83 Fat loss at the site of prior insulin infusion sites, lipoatrophy, is less common and has been seen more frequently in those with multiple autoimmune diseases. 84 Both of these findings are categorized as lipodystrophy and earlier studies have shown a greater risk of these issues in those with higher insulin autoantibodies. 85 Lipodystrophy can impact how insulin is absorbed and thus lead to deterioration in glycemic control.…”
Section: Complications Of Pump Therapy: Infusion Sets and Hypertrophymentioning
confidence: 99%
“…[153] It is an immunological response to insulin aggregates in the presence of high circulating titers of anti-insulin autoantibodies. LA was more prevalent in the prehuman-insulin era due to the use of animal insulin.…”
Section: Adverse Events Of Faulty Techniquementioning
confidence: 99%
“…Though it was commonly encountered among patients taking animal insulin, with the introduction of recombinant human insulin, it has become rarer. Treatment with analogue insulin has further reduced the incidence (1). Due to incompletely understood pathogenesis, lipoatrophy remained a vexing problem to physicians.…”
Section: Introductionmentioning
confidence: 99%